Rodzina w sytuacji choroby. Wpływ choroby psychicznej na funkcjonowanie rodziny w wielkim mieście (na przykładzie Chorzowa) - Przywarka, Irena (Wydawnictwo Naukowe UAM, 2002)
The aim of the work was showing the changes that take place in the families in the particularly difficult situation that mental disease /schizophrenia/ of one of their members is. This work is an attempt of better understanding of all the cultural conditions and possibilities of dwelling and functioning of family in a mental disease case. The structure /especially generation stuctures/, the member’s roles and positions and the among - family relations have been analysed. The changes taking place in the field of family’s functions have been described as well as the ralation between the family and the outher environment. Results o f investigations permited on drawing out the conclusion, that the fact of psychiatric disease and resulting from it no social and emotional adaption o f ill person causes changes in range of all functions of family .It is important to point the contrary relationship that means the family influence modyfing the illness lasting period and determining treatment’s success.
Family’s situation when disease strikes. The influence of the psychic disease on the funtioning of family in a large city (on the expample of Chorzów)